Non-Proliferasi: Problematika Hukum Penggunaan Tenaga Nuklir pada Kapal Selam Militer - Mainaldi, Billy (Uti Possidetis: Journal of International Law, 2023)
This article proves that the AUKUS pact has violated the 1968 Non-Proliferation Treaty (NPT). The AUKUS Pact is a cooperation agreement between Australia, Britain and the United States in the development of technology in the defense sector, including the transfer of technology for powered submarines in it. This article uses a normative juridical method with the main source being legal materials containing normative legal rules, and uses statue approch which is Treaty on the Non-Proliferation of Nuclear Weapons (NPT) and Australia-United Kingdom-United States Partnership (AUKUS). In the discussion, it was found that the state parties to the AUKUS pact had violated the NPT, this was evidenced by the transfer of technology for powered submarines with the use of high-grade uranium in the range of 93-97.3%. While the use of uranium above 90% can be categorized as weapons grade. Therefore, the actions of the state parties to the AUKUS pact have violated articles 1 and 2 of the NPT, wherein Nuclear Weapon States (NWS) and Non-Nuclear Weapon States (NNWS) are prohibited from transferring or receiving transfers of nuclear weapons technology in any form. For this reason, this article suggests adding an additional sanction clause to the NPT as well as a revision to Article 10 of the NPT. the addition of sanctions and the revision of article 10 are needed to strengthen the joint commitment of the NPT countries in carrying out the proliferation of nuclear weapons.